2009
DOI: 10.1007/s11430-009-0068-1
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotope evidence for tracing the diet of the host Hepialus larva of Cordyceps sinensis in the Tibetan Plateau

Abstract: Two types of Hepialus larvae with different diets were distinguished in the Sejila Mountain, TibetanPlateau based on the stable carbon isotope data of the host Hepialus larva of Cordyceps sinensis and its closely adjacent tender plant roots and humus fractions. Type I is the larva chiefly fed by soil humus, and characterized by the δ 13 C values of −22.6‰ to −23.4‰, and more than −23.4‰ in its heads. Type II is the larva chiefly fed by tender plant roots, and characterized by the δ 13 C values of −24.6‰ to −27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 14 publications
(14 reference statements)
2
26
0
Order By: Relevance
“…It can be seen from Fig. 4 that there is an obvious variation of the δ 13 C values from plants to host larvae, and to C. sinensis on the basis of our previous [24] and newly-obtained data. Thitarodes larva, which generally lives in deeper soils and mainly feed on the tender roots of C3 plants [1], is the specific host of O. sinensis.…”
Section: δ 13 C Values Of Individual Major Fatty Acids Of Neutral Andsupporting
confidence: 53%
See 2 more Smart Citations
“…It can be seen from Fig. 4 that there is an obvious variation of the δ 13 C values from plants to host larvae, and to C. sinensis on the basis of our previous [24] and newly-obtained data. Thitarodes larva, which generally lives in deeper soils and mainly feed on the tender roots of C3 plants [1], is the specific host of O. sinensis.…”
Section: δ 13 C Values Of Individual Major Fatty Acids Of Neutral Andsupporting
confidence: 53%
“…Thus, C18:2 in C. sinensis was originated both from the host larva and de novo synthesis. However, the host larva was unable to biosynthesize C18:2 [35,36], and had to assimilate C18:2 only from the tender roots of plants, especially Polygonum macrophyllum and Polygonum viviparnm, which were considered to be its favorite food with the δ 13 C value lower than that of the predator larva [24]. In the de novo synthesis of C18:2, the 13 C-depleted C18:1 in C. sinensis was preferred to be desaturated.…”
Section: Stable Carbon Isotope Fractionation In the Lipids Of C Sinementioning
confidence: 99%
See 1 more Smart Citation
“…They develop into infective conidia, which gradually infiltrate into deeper soils mainly due to rainfall. The host 3 , a healthy Thitarodes (Lepidoptera: Hepialidae) larva, will overwinter in the alpine grass lands in the Qinghai-Tibetan Plateau and its adjacent high-altitude areas 4 , 5 , go deep into the roots of Polygonum knotweed, Kobresia sedges or Astragalus milk-vetch, and safely nestle in the roots of its favorite foods 6 . It may be infected by the fungus in the soils through the mouth or the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to develop new methods and search for sensitive indicators to detect geographical origin. Cordyceps sinensis occurs on the Tibetan Plateau and its adjacent high-altitude areas characterized by low ambient temperatures [12], [13].And its lipid composition may be a sensitive marker reflective of its living environment. Lately, it has been found that the fatty acid composition in lipids may be used to access geographic origin.…”
Section: Distributionmentioning
confidence: 99%